Strategic Priorities for the Establishment of Construction Materials Manufacturing Enterprises in the Context of Large-Scale Infrastructure Reconstruction - Koshovy, B. (Ways to Improve Construction Efficiency, 2025)
The article examines methodological approaches to assessing the capacity of the construction materials market in the context of large-scale infrastructure reconstruction in Ukraine. It is substantiated that current economic recovery conditions generate a significant increase in demand for construction industry products, which necessitates the improvement of approaches to their quantitative and structural assessment. An approach to determining the market capacity of construction materials is proposed based on the analysis of reconstruction volumes, standard material intensity of construction, and the structure of infrastructure projects. The structure of demand for key types of construction materials, including concrete, metal structures, road mixtures, and energy-efficient insulation materials, is systematized. It is established that the projected demand for construction materials significantly exceeds existing production capacities, leading to structural deficits in certain market segments. The main bottlenecks in the development of the construction industry are identified, including limited production capacities, dependence on imports of certain types of products, and logistical constraints. The necessity of forming strategic priorities for the establishment of construction materials manufacturing enterprises is substantiated, taking into account economic, technological, and regional factors. The need to move away from traditional linear and centralized models of industrial location toward the formation of a network of local production hubs is justified. The expediency of forming strategic priorities for the creation of construction materials manufacturing enterprises based on the principles of the circular economy is substantiated, which will reduce resource dependence, increase the efficiency of material use, and ensure the sustainable development of the construction industry. An original model for integrating mobile recycling complexes for demolition waste directly into the production cycle of new materials is proposed. This approach ensures not only the economic efficiency of reconstruction (cost reduction by 20–40%) but also complies with environmental sustainability principles and the requirements of the European Green Deal.